Analisis Peran Audit Internal Terhadap Pencegahan Serta Pendeteksian Kecurangan (Fraud): Literatur Review Artikel Terindeks Sinta - Indriyani Astuti Nurachman; Harry Z. Soeratin (GLOBAL SCIENTS PUBLISHER, 2024)
In addition to its positive effects, the advancement of accounting science in Indonesia includes drawbacks for some people. The incidence of fraud is among the adverse consequences. By examining the literature review, this study aims to ascertain or test the impact of internal audit's function on accident (fraud) detection and prevention. Using information from 15 publications that Sinta indexed between 2018 and 2024, this study provides detailed insights into how internal auditing plays a role in preventing and detecting situations (fraud). Using literature observation, this study reviews the literature using a qualitative descriptive method. These statistics demonstrate how internal auditing can assist a business in identifying and averting fraud.